ARE THERE HEALTH DISPARITIES AMONG JORDANIAN OLDER ADULTS? POTENTIAL FACTORS (PART 1) - Hayajneh, Audai (European Scientific Journal, ESJ, 2015)
Older adults in Jordan are confronted with emerging health issues. They have diabetes, hypertension, chronic heard diseases and other conditions causing them to have a poor quality of life compared to other segments of Jordanian population and others in neighbor countries, such as North Africa and Arab countries. This paper will shed light on the health variables and challenges that Jordanian older adults have vis-à-vis biologic, genetic, socio-cultural, environmental factors, health behaviors, and health literacy. Such issues that may be potential seeds of health disparities, placing older adults at higher risk for adverse health outcomes in comparison with other age groups in Jordan as well as their counterparts in surrounding countries.